Penyuluhan Digital Marketing dan Pembuatan Website untuk Memasarkan Produk Gerabah di Desa Bumijaya Kabupaten Serang - Wibowo, Hermansyah; Wibowo, Hermansyah Andi; Suhaemi, Muhamad (Jurnal Abdimas Nusantara, 2025)
Bumijaya Village is a village in Ciruas District, Serang Regency, a village that is a pottery center. The main advantage of this village lies in its high-quality Natural Resources (clay). However, this natural advantage is not managed optimally so that the economic added value obtained by pottery craftsmen is also not optimal. One of the weaknesses is the low ability to communicate with potential markets for pottery products. The impact is that sales of pottery products are stagnant and not varied. Therefore, in this community service, we provide counseling related to the importance of understanding and practicing product promotion while creating a website for the residents of Bumijaya Village. Video tutorials for prospective customers that can be used to search for products, choose, and make transactions are also published on www.youtube.com